The multiplicity Issue in phonetic Terminology in University Linguistic Studies: إشكاليّة تعدّد المصطلح الصّوتي في الدّرس اللّساني الجامعي - Kezouli , Rahma (Maalim, 2025)
The twentieth century marked significant advancements and revolutionary changes in the field of linguistics, leading to the introduction of new Western terminology within this domain of knowledge. It became imperative for Arab scholars to devise equivalents for these novel linguistic terms. However, the individual efforts coupled with a lack of standardized approaches for their development and translation resulted in considerable terminological confusion, creating multiple equivalents for a single foreign term. Specifically, the phonetic term, a crucial element in linguistic research, has been affected by this multiplicity, which hinders the understanding and assimilation of phonetic studies. This research paper seeks to explore the phenomenon of terminological multiplicity, a critical issue that has emerged as a significant challenge in contemporary Arabic linguistic studies. This issue presents a formidable barrier for both Arab researchers and university students. What are the causes of this multiplicity in terminology? And what are its implications on university education?